2018
DOI: 10.1093/jee/toy250
|View full text |Cite
|
Sign up to set email alerts
|

Field Study Investigating Cry51Aa2.834_16 in Cotton for Control of Thrips (Thysanoptera: Thripidae) and Tarnished Plant Bugs (Hemiptera: Miridae)

Abstract: Field experiments were conducted in 2016 and 2017 in Tennessee to evaluate the effects of a novel Bacillus thuringiensis (Bt)-transgenic toxin, Bt Cry51Aa2.834_16, on thrips (Thysanoptera: Thripidae) and tarnished plant bug, Lygus lineolaris (Palisot De Beauvois) (Hemiptera: Miridae), in cotton. Protection from thrips injury with the Bt trait was as good or better than an insecticide-based approach. The use of the Bt trait resulted in reduced numbers of immature tarnished plant bug, particularly large nymphs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 22 publications
4
43
2
Order By: Relevance
“…This result suggests that adult females of both species can detect and avoid the presence of MON 88702 expressed in cotton seedlings. Because MON 88702 had limited acute adult toxicity, these behavioral differences may be the most significant factor driving differences in F. fusca damage observed in field studies measuring efficacy …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…This result suggests that adult females of both species can detect and avoid the presence of MON 88702 expressed in cotton seedlings. Because MON 88702 had limited acute adult toxicity, these behavioral differences may be the most significant factor driving differences in F. fusca damage observed in field studies measuring efficacy …”
Section: Resultsmentioning
confidence: 88%
“…Because MON 88702 had limited acute adult toxicity, these behavioral differences may be the most significant factor driving differences in F. fusca damage observed in field studies measuring efficacy. 11,12,14…”
Section: Oviposition Choice Of F Fusca and F Occidentalis On Mon 88mentioning
confidence: 99%
See 2 more Smart Citations
“…MON 88702 should also extend the useful life of other insecticides by reducing the exposure of tarnished plant bug to current insecticides, resulting in a decreased rate of selection for resistance. MON 88702 is not expected to be 100% effective on tarnished plant bug, but previous research showed a reduction in the number of sprays needed for tarnished plant bug in cotton when sprayed at the current action threshold ( Graham and Stewart 2018 ). Research is needed to determine at what population density this event provides effective control of tarnished plant bug without sustaining economic loss.…”
mentioning
confidence: 99%